Craniofacial surgery simulation using volumetric object representations - Rana, Mohammad Azam; Setan, Halim; Majid, Zulkepli; Chong, Albert K. (2006)
Computer Assisted Surgery (CAS) systems facilitate surgical planning and analysis by aligning various datasets with information on morphology (MRI, CT, MR angiographies), cortical function (fMRI) or metabolic activity (PET, SPECT). These systems are categorized into performing one or more of the functions such as data analysis, surgical planning and surgical guidance, etc. The surgical planning systems present surgeons with data gathered prior to surgery and facilitate in plotting an approach trajectory that avoids critical structures such as blood vessels etc. Computer tomography (CT) has been widely used for surgical planners as craniofacial anomalies and fine anatomic details of facial traumic injuries are well studied with CT. This research focuses on development of a system for simulation of craniofacial reconstruction surgery based on CT and laser scan data. The surfaces of soft tissue and hard tissue have been extracted from CT data using Marching Cubes algorithm and are rendered with surface based methods. Cutting of soft/hard tissue has been performed using cutting surface. Various rendering modes (surface, wireframe, point cloud) for soft/hard tissue have been implemented for better diagnostic visualization. This paper reports various components of the system and the current state of the integrated system.